2017
DOI: 10.1186/s40560-017-0228-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of contact system in septic shock: the next target? An overview of the current evidence

Abstract: BackgroundSeptic shock remains challenging to intensive care units worldwide, despite recent documented improvement in mortality over the years. Multiple new therapies have been attempted without success in large clinical trials. Evidence concerning the role of the contact system and bradykinin on septic shock physiological manifestations is shown by this article.ObjectivesThe objective of the study is to review the current evidence linking contact system activation and septic shock, as well as efficacy of ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…PK, which circulates in a noncovalent complex with HK 6 , cleaves HK and the proinflammatory peptide bradykinin is released 7 . In severe sepsis, activation of the contact system is archetypal 8 and multiple animal studies with different pharmacological interventions that inhibit FXII, bradykinin receptors or the interaction of contact factors with the bacterial surface 9 were done to evaluate potential therapeutic options 10 . However, surprisingly little is known about the precise role of contact factors during microbial sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…PK, which circulates in a noncovalent complex with HK 6 , cleaves HK and the proinflammatory peptide bradykinin is released 7 . In severe sepsis, activation of the contact system is archetypal 8 and multiple animal studies with different pharmacological interventions that inhibit FXII, bradykinin receptors or the interaction of contact factors with the bacterial surface 9 were done to evaluate potential therapeutic options 10 . However, surprisingly little is known about the precise role of contact factors during microbial sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…We did not find any correlation between bradykinin and cardiovascular SOFA score, which calls into question a role of bradykinin in the maintenance of persisting failing circulation accompanying established sepsis. Our findings could thus explain the beneficial effect of bradykinin receptor antagonists when given within an hour after induction of experimental sepsis in animal models (33,34). This is opposed to the disappointing results found when evaluating the potent bradykinin-2 receptor (B 2 R) antagonist, deltibant, for treatment of sepsis in the clinical setting with a significant delay before initiation of treatment (32).…”
Section: Discussionmentioning
confidence: 88%
“…Since the presumably harmful effects of bradykinin could be targeted with pharmacological therapy , these observations ought to be verified in a general ICU population with sepsis caused by a wider array of pathogens. In the present clinical prospective matched observational study, we therefore tested the hypothesis that plasma levels of bradykinin are increased in patients with sepsis of a severity requiring intensive care.…”
mentioning
confidence: 99%
“…Results from other studies on targeting the contact system in systemic infections (summarized in ) were not unambiguous: two rat models for sepsis showed that administration of soy bean trypsin inhibitor (SBTI, a PK antagonist), as well as a B1R antagonist, attenuated hypotension and mortality, respectively. Antagonism of B2R was therapeutic in a porcine sepsis model for Pseudomonas aeruginosa , but not for Neisseria meningiditis .…”
Section: Past and Present: The Contact System In Sepsismentioning
confidence: 98%